2016
DOI: 10.1186/s40795-016-0108-0
|View full text |Cite
|
Sign up to set email alerts
|

Research needs and prioritizations for studies linking dietary sugars and potentially related health outcomes

Abstract: Background: Relationships among dietary sugars and a variety of chronic diseases have spawned interest in investigating the metabolic effects of dietary sugars. An approach developed by the Agency for Healthcare Research and Quality (AHRQ) for assessing Future Research Needs (FRN) was implemented with modifications that integrated an evidence mapping process. Methods: A panel of 14 stakeholders across 7 pre-defined areas of expertise (lay audience, policy makers, health providers, research funders, evidence-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…On the basis of these results, we concluded that the research trends and research gaps have not changed since 2013, when the evidence-map database was updated. Therefore, the 14 prioritized research questions (research needs) in the broad field of dietary sugars and health outcomes remain valid ( Supplemental Table 2 ) ( 11 ). These 14 high-priority research questions were identified by a multidisciplinary stakeholder panel following a structured approach that integrated evidence mapping with expertise or viewpoints from the panel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of these results, we concluded that the research trends and research gaps have not changed since 2013, when the evidence-map database was updated. Therefore, the 14 prioritized research questions (research needs) in the broad field of dietary sugars and health outcomes remain valid ( Supplemental Table 2 ) ( 11 ). These 14 high-priority research questions were identified by a multidisciplinary stakeholder panel following a structured approach that integrated evidence mapping with expertise or viewpoints from the panel.…”
Section: Discussionmentioning
confidence: 99%
“…Search results were limited to English-language, peer-reviewed human intervention studies and prospective cohort (PC) studies published from January 2013 to December 2016 ( Supplemental Table 1 ). This was the same search strategy and study eligibility criteria utilized in creating the 2013 evidence-map database ( 11 ). We did not search for or include any unpublished studies, clinical trial registries, or gray literature such as government or organization reports.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A diet high in added sugars has been linked to a variety of health problems, including obesity [4], cardiovascular disease [5] and type 2 diabetes [6]. Despite the causal relationship reported between total and added sugars intake and a variety of chronic diseases, there exists some uncertainties as to the accuracy of these conclusions [7,8]. Research prioritization for studies that link dietary sugars with potentially related health outcomes continues to be an important area of investigation [9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, nutrition-related systematic reviews only comprise ∼8% of all systematic reviews in the Cochrane Database of Systematic Reviews and, among these, approximately half focus on nutritional supplementation or supplements ( 3 ). Due to the anticipated need to consider broader research questions for public health nutrition, we previously modified the ARHQ's FRN approach by integrating an evidence-mapping process ( 4 ). Evidence mapping is an emerging evidence synthesis method for describing the volume and characteristics of research in a broad field.…”
Section: Introductionmentioning
confidence: 99%